Modeling higher order thinking skills and metacognitive awareness in English reading comprehension among university learners - Aziz, Musharraf; Rawian, Rafizah (Frontiers in Education, 2022)
This study aimed to examine the levels of Pakistani university learners' higher order thinking skills (HOTS) in English reading comprehension and to explore how explicit assessments of HOTS can reveal learners' strengths and weaknesses in reading as compared to the traditional assessment of reading. Secondly, the study analyzed the effect of learners' metacognitive awareness on reading on the relationship between their HOTS levels and reading performance. It used a mixed-method approach. In the quantitative phase, an explicit HOTS-based reading test was designed using Bloom's taxonomy. Using random stratified sampling, it was administered to the learners of Bachelor of Science in English (n = 200). Stratified sampling was performed for investigating the gender gap in HOTS levels. The learners' metacognitive awareness of reading was analyzed using Survey of Reading Strategies. Descriptive analysis, independent sample t-test, correlation analysis, and moderator analysis were conducted. It was found that the learners' HOTS levels correlated with their reading performance where creative skill was the strongest, and evaluating skill was the weakest. Metacognitive awareness of reading positively moderated the relationship between the learners' HOTS levels and reading performance. In the qualitative phase, purposive stratified sampling was applied. A subsample (n = 6) was extracted from the core sample based on the high, average, and low reading performance, and three groups were formed. A semi-structured interview was conducted to know learners' opinions on using HOTS-based assessment in reading and their cognitive and metacognitive abilities. The thematic analysis of the qualitative data revealed that three out of six learners did not approve of the way they were assessed by the university. They informed that they had issues with cognitive and metacognitive control of English texts. The findings revealed that the majority of learners suffered low HOTS levels in English reading. The study offers recommendations for English as a second language (ESL) teachers, assessors, and policymakers to improve learner performance to the possible optimal level, especially in underdeveloped contexts that use traditional reading assessments.